(untitled) - Abbas Abdollahi; Elaheh Ahmadi; Abdolrasol Zakerin (Fasa University of Medical Sciences, 2014)
Because of the absence the specific standards for antibacterial effects evaluation of herbs and challenges in this field, some notes on the main problems in standardization of these procedure have been regarded: the weight of medical herbs according the use of herbs based on the recommendations of the traditional medicine, study on related standard bacteria, applying of essence or herb extract, suitable extraction method, type of solvent in extraction, the time of harvesting plant and confirmed by an expert in herb, reliable methods of microbiological research and drug sensitivity, and finally, use of standard antimicrobial drugs as a benchmark to compare